CRAC (computer room air conditioner) positioning for Sun HPC data center - Xu, Qianru (2019)
This project aims to present a few of computational fluid dynamics (CFD) analyses of the server room at Changi Airport HPC data center, with different positioning layout arrangements to obtain more energy savings and better cooling efficiency. The CFD models based on energy equations and thermal mass were used for simulation by ANSYS FLUENT software. Parameters data for temperature, velocity, and vector distributions were studied to predict heat distribution in a data center and also to determine a better layout of the cooling schemes. The CFD simulation results highlighted those hotspot temperature zones among the data center server racks and provided the comprehensive data center 3D ANSYS CFD thermal mapping and the cold/hot air movement of the data center. The results were also offered a temperature distribution for the computer room air conditioning (CRAC) units return outlet temperature. By using the results in this project, a better understanding and optimization of cooling strategies and several recommended solutions could improve the design of future data centers.